Innovating education: a comprehensive review of STEM education approaches - Marzuki, Omar Faruqi; Lih, Ellie Teo Yi; Zainol @ Abdullah, Wan Nor Zanariah; Khairuddin, Nozieana; Inai, Nor Hanifawati; Md Saad, Juniza; Abdul Aziz, Mohd Hamim (Human Resources Management Academic Research Society (HRMARS), 2024)
This comprehensive paper delves into the evolving realm of STEM (Science, Technology, Engineering, and Mathematics) education, a critical component in the modern educational landscape. The review highlights how STEM education has transcended the mere combination of four subjects into an integrated, interdisciplinary approach essential for developing key skills like critical thinking and problem-solving. The paper highlights the necessity of STEM in preparing students for the complexities of the 21st century, driven by a technology-oriented global economy and the demand for innovative and analytical skills. The review explores the challenges faced in STEM education, such as access and equity issues, the need for specialized educator training, and student engagement. The impact of STEM on student performance, skill development, and workforce preparedness is analyzed, highlighting how it contributes to individual career prospects and broader economic and societal advancement. The review presents case studies of successful STEM programs across different education levels and compares international STEM education models, providing insights into effective strategies and diverse educational philosophies. Lastly, the paper identifies emerging trends in STEM education, including the integration of AI and machine learning, a focus on sustainability, and the incorporation of arts (STEAM). It concludes with recommendations for policy and practice, advocating for increased accessibility, interdisciplinary learning, and continuous professional development for educators to ensure STEM education remains relevant and effective.